Syndrome of intraabdominal hypertension: pathophysiological aspects and surgical problems - S. A. Aliev; E. S. Aliev; T. B. Sadykzade; M. M. Kerimov; E. G. Tagiev (Клінічна хірургія)
Syndrome of intraabdominal hypertension: pathophysiological aspects and surgical problems